Kepemimpinan Ideal Pada Organisasi di Era Milenial - Danang Nugroho; Dina Sakinah; Asri Fatimah; Dini Indria Zahira; Didah Paridah; Helmalia Nur Fauziah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Leadership is a vital element of the management process, no exception in any organization. The leader acts as a captain, designing and managing existing resources, as well as directing other people to achieve good performance. The leadership style applied and the level of satisfaction of subordinates are determining factors in measuring leadership success. Leadership will play a crucial role in the success of an organization. This is due to the important role of leadership in facilitating significant change in organizations, making leadership an impactful force, and considering leadership as the art of managing organizational conformity and stability. In the era of the younger generation, good government is created when the leader meets the qualifications. However, a good leader must also have integrity, honesty and loyalty to the public. Millennial leadership must encourage the independence and entrepreneurial spirit of the younger generation. Nation development must be based on independence and entrepreneurship.